Is Felix Salten the author of the Mutzenbacher novel (1906)? Yes and no. (May 2022) - Rebora, Simone; Salgaro, Massimo
Josefine Mutzenbacher oder die Geschichte einer Wienerischen Dirne von ihr selbst erzählt, published in Vienna in 1906, represents one of the most fascinating cases of attribution of authorship in German literature. Although Josefine Mutzenbacher is usually attributed to Felix Salten, the author of the world-famous Bambi (1923), the novel's authorship has never been confirmed, and many other candidates have been named as potential authors. Among them is Arthur Schnitzler, who published Reigen, a cycle of amorous adventures in Viennese society, in 1903. Some scholars, instead, have attributed the novel to such lesser-known writers as Ernst Klein and Willi Handl. The controversy surrounding the authorship of Josefine Mutzenbacher was the starting point for our stylometric analyses, and our results help to answer some unresolved questions in a debate that has lasted for more than 100 years. The analyses were performed using the R package Stylo, which enables an efficient application of Burrows' Delta and its variants. Focusing on both the entire text and on the final pages, two different types of analysis were carried out: one combines 1200 different stylometric methods to compare the candidate authors Salten, Schnitzler, Bahr, Altenberg, Hofmannsthal, Klein and Handl; the other verifies the attribution using the 'impostors' method. The results show that the most probable author is Felix Salten, while none of the candidates could be identified as the author of the final pages, confirming the hypothesis that the text was left unfinished by Salten and completed by an as-yet-unidentified ghost-writer.